2008
DOI: 10.1001/archderm.144.8.1062
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients With Universal Vitiligo and Health-Related Quality of Life

Abstract: Comment. This small monocentric study cannot validate or devalue the Skindex-29 2 as a measure for QOL in CLE. The correlation between what physicians and patients perceive as objective improvement or deterioration of a skin condition may not correlate with the patient's QOL. Our observations may imply that our treatment goals should extend beyond the obvious control of the disease, which is reliably measured by the CLASI. 1 Quality of life does not uniformly improve as the activity of the disease wanes. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The Skindex total score can be interpreted as having very little effect (score ≤ 5), mild effect (scores 6–17), moderate effect (scores 18–36) and severe effect (scores ≥ 37) on QoL 118 . The Skindex‐29 was administered in 15 studies 33,39,118–130 . Among studies that reported mean global scores in the overall population, scores ranged from 20.8 to 33.1 39,121–123,125 ; these scores indicate that vitiligo had moderate effects on patients’ lives (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Skindex total score can be interpreted as having very little effect (score ≤ 5), mild effect (scores 6–17), moderate effect (scores 18–36) and severe effect (scores ≥ 37) on QoL 118 . The Skindex‐29 was administered in 15 studies 33,39,118–130 . Among studies that reported mean global scores in the overall population, scores ranged from 20.8 to 33.1 39,121–123,125 ; these scores indicate that vitiligo had moderate effects on patients’ lives (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 118 The Skindex‐29 was administered in 15 studies. 33 , 39 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 Among studies that reported mean global scores in the overall population, scores ranged from 20.8 to 33.1 39 , 121 , 122 , 123 , 125 ; these scores indicate that vitiligo had moderate effects on patients’ lives (Fig. 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…In more than 50% of cases, the disease onset is prior to the age of 20 years 3 and is progressive especially in the first 10–20 years 4 . Although the disease usually does not cause any objective physical complaints, it is associated in the majority of patients with marked limitations of health‐related quality of life (QoL) 5,6 . This results apparently from a perceived stigmatization 7 especially in cases where the disease affects visible parts of the body or the genitals.…”
mentioning
confidence: 99%
“…Patients with vitiligo develop white patches on their skin, including in visible areas such as the face, neck, hands, and forearms. As a result, the quality of life of vitiligo patients can be severely reduced (2)(3)(4)(5). Clinically two major types of vitiligo are recognized: segmental vitiligo (SV), which affects a localized asymmetrical area of the body, and nonsegmental vitiligo (NSV), the more common subtype, which often involves multiple body sites in a symmetrical fashion.…”
Section: Introductionmentioning
confidence: 99%